One-step introduction of ZrC-SiC inside carbon fabric to fabricate high homogeneous and damage-tolerant composite inspired by vibration. Issue 7 (July 2019) - Cheng, Yuan; Hu, Ping; Zhang, Wenzheng; Ma, Chen; Feng, Jiaxin; Fan, Qingpu; Zhang, Xinghong; Du, Shanyi
Abstract: The ZrC-SiC ceramics were introduced inside carbon fabric uniformly in one-step by vibration assisted injection. This novel method achieved a relative density of green body at 45%, nearly 50% higher than that of without vibration. The composite obtained a rivaling flexural strength at 185 ± 12 MPa, graceful fracture mode with fracture toughness at 5.86 ± 0.16 MPa∙m 1/2 and work of fracture reaching 1284 J/m 2, 2 times of the value without vibration. By comparison, a poor fracture toughness and mediocre flexural strength of 4.05 ± 0.27 MPa∙m 1/2 and 113 ± 19 MPa are equipped with the non-vibration treated one.